Implikatur Percakapan dalam Tayangan “ Tiga Bacapres Bicara Gagasan” - Simanjuntak, Dairi Sapta Rindu; Wulan, Eka Putri Saptari; Gustianingsih, Gustianingsih (Asosiasi Ide Bahasa Kepri, 2024)
The context of conversation in a discourse, especially political discourse which is currently trending, is very interesting to discuss. The context of conversation in pragmatics studies can be observed from the concept of implicature. Therefore, this research aims to explore the form of implicature utterances and the meaning of implicatures contained in the dialogue between the 2024 presidential candidates on the